2000
DOI: 10.1073/pnas.140216197
|View full text |Cite
|
Sign up to set email alerts
|

Normotonic cell shrinkage because of disordered volume regulation is an early prerequisite to apoptosis

Abstract: A major hallmark of apoptosis is normotonic shrinkage of cells. Here, we studied the relation between apoptotic cell shrinkage and apoptotic cell death. Induction of the apoptotic volume decrease (AVD) under normotonic conditions was found to be coupled to facilitation of the regulatory volume decrease (RVD), which is known to be attained by parallel operation of Cl ؊ and K ؉ channels, under hypotonic conditions. Both the AVD induction and the RVD facilitation were found to precede cytochrome c release, caspas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

47
783
5
5

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 672 publications
(840 citation statements)
references
References 34 publications
47
783
5
5
Order By: Relevance
“…Our observation of cytochrome c release even in high K þ medium could not agree with earlier reports that insisted elevated K þ inhibits apoptosis before mitochondrial perturbation. 16,17 This variation might have arisen due to the existence of multiple pathways of cytochrome c release governed by the nature of apoptotic stimuli and cell type. 23 A recent study has shown that 80 mM extracellular K þ markedly attenuated though never completely prevented the cytochrome c release from mitochondria in human neutrophils.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our observation of cytochrome c release even in high K þ medium could not agree with earlier reports that insisted elevated K þ inhibits apoptosis before mitochondrial perturbation. 16,17 This variation might have arisen due to the existence of multiple pathways of cytochrome c release governed by the nature of apoptotic stimuli and cell type. 23 A recent study has shown that 80 mM extracellular K þ markedly attenuated though never completely prevented the cytochrome c release from mitochondria in human neutrophils.…”
Section: Resultsmentioning
confidence: 99%
“…The results are inconsistent with others, which propose that blockage of K þ efflux also suppresses cytochrome c release. 16,17 The reasons for this discrepancy are presently unclear. A huge variation regarding the effect of K þ efflux on apoptosis depending upon cell type and nature of apoptotic insult 30 and similar diversities in the pathways of cytochrome c release might have contributed to these contrasting findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 An early morphological alteration occurring during apoptosis is cell shrinkage, which is associated with an increased cellular efflux of K þ and Cl À ions. [2][3][4][5][6][7][8] The reduced intracellular K þ concentration also facilitates the activation of apoptosisrelated proteases -the caspases. 9,10 Conversely, blocking K þ or Cl À channels prevents cell shrinkage and cell death.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Conversely, blocking K þ or Cl À channels prevents cell shrinkage and cell death. [5][6][7][8] While the K þ efflux depends on an increased number of active K þ channels in the plasma membrane, less is known about the Cl À efflux.…”
Section: Introductionmentioning
confidence: 99%